2016
DOI: 10.1021/acsami.5b09912
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatments for Multifunctional Property Enhancement of Carbon Nanotube Fibers from the Floating Catalyst Method

Abstract: We investigated the effects of the synthesis conditions and condensation processes on the chemical compositions and multifunctional performance of the directly spun carbon nanotube (CNT) fibers. On the basis of the optimized synthesis conditions, a two-step post-treatment technique which involved acidification and epoxy infiltration was also developed to further enhance their mechanical and electrical properties. As a result, their tensile strength and Young's modulus increased remarkably by 177% and 325%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…The most common methods for integrating conductive materials into soft polymer filaments include coating with metal or carbon 21, 25 , or with conductive composites of polymer with graphite, carbon, metal nanoparticles, or other conductive materials 13, 15, 23, 24, 2629 . This can yield devices that are useful as strain (stretch) sensors, but that may not admit other functionalities (such as contact sensing, as demonstrated here).…”
Section: Introductionmentioning
confidence: 99%
“…The most common methods for integrating conductive materials into soft polymer filaments include coating with metal or carbon 21, 25 , or with conductive composites of polymer with graphite, carbon, metal nanoparticles, or other conductive materials 13, 15, 23, 24, 2629 . This can yield devices that are useful as strain (stretch) sensors, but that may not admit other functionalities (such as contact sensing, as demonstrated here).…”
Section: Introductionmentioning
confidence: 99%
“…Small-molecule functionalized with electron beam irradiation improved the tensile strength by 25% upon functionalization, and a total increase of 88% tensile strength was observed when irradiated with the electron beam after functionalization [47]. In a report, recently it was found that mechanical strength of CNT yarns can improve by acid treatment followed by epoxy treatment [48]. Moreover, a maximum stiffness of 62.0 GPa was recorded.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…[138] Other force measuring technologies for surgical robotic systems are available. [112,124,127,[141][142][143][144] Hybrid configurations between two or more force sensing technologies are available. For example, biofeedback sensors can be integrated into surgical tools to monitor the oxygen saturation levels of the tissue and alert a surgeon if the oxygen level is below an acceptable level while strain gauges can be used to measure the applied force of surgical tools.…”
Section: Force Sensing For Surgical Roboticsmentioning
confidence: 99%